Theory-derived intervention to improve oral health of older adults: study protocol for a randomised controlled trial - Patrick Finbarr Allen; Xiaoli Gao; Mun Loke Wong; Ashish Chetan Kalhan; Joshua Jiaming Xie; Hamzah Siti Hajar; Alvin Boon Keng Yeo (BMJ Open)
Introduction Changing health behaviours is an important and difficult task. Despite growing interest in behavioural theories and models, there is a paucity of research examining their validity in explaining oral health behaviours, and there is a need for interventional studies to assess their effectiveness in improving oral health. This study aims to test the explanatory power of the dominant psychological theories, develop theory-derived intervention and evaluate its effectiveness in improving oral health of older adults.Methods and analysis 440 community dwelling older adults will be recruited. To be eligible for this trial, one needs to be 55–79 years old, having at least 8 natural teeth, and with no life-threatening disease, impaired cognitive function, or radiotherapy in the head and neck region. At the initial visit, each participant will be required to complete a detailed questionnaire which collects information on sociodemographic background, oral health behaviours and domains of three psychological theories and models: (1) health belief model, (2) theory of planned behaviour and (3) social cognitive theory. The theory or model that best explains the health behaviours will be selected for designing the oral health intervention. The effectiveness of the theory-derived intervention will be evaluated in a randomised controlled trial. Participants will be randomly assigned to two groups, receiving theory-derived intervention and conventional health education, respectively. At baseline and at 12 and 24 months post intervention, each participant will complete a short questionnaire and undergo an oral examination (dental check-up). The effectiveness of the interventions will be evaluated using behavioural outcomes (diet, toothbrushing, interdental cleaning) and clinical outcomes (oral hygiene, dental caries and periodontal conditions).Ethics and dissemination This study has been approved by the Institutional Review Board of National University of Singapore (Ref: NUS-IRB-2020-417). Findings will be presented in international conferences and peer-reviewed journals.Trial registration number NCT04946292.